Combining cartilaginous microtissues primed under altered oxygen environments with melt electrowritten meshes to engineer scaled-up grafts - Kelly, Daniel (My University, 2026)
Current articular cartilage tissue engineering strategies fail to produce grafts that recapitulate the complex zonal composition and organisation of the native tissue. Developmental engineering strategies might overcome such limitations, leading to the generation of more biomimetic grafts by mimicking key steps of normal tissue development. One such approach leverages the capacity of stem/progenitor cells to self-organise into microtissues or organoids, which can be used as the building blocks of larger grafts. In this study, adult human bone marrow-derived mesenchymal stem/stromal cells (hMSCs) were used to engineer phenotypically distinct hyaline cartilage microtissues for the modular assembly of zonally defined grafts. Altered oxygen (O2) levels, within the physiological range, were first explored to modulate the microtissue phenotype. Melt electrowritten (MEW) meshes were then used to guide the fusion of such microtissues into scaled-up grafts. Priming hMSC-derived microtissues at oxygen levels representative of different regions of the native tissue supported the development of distinct cartilaginous phenotypes. In addition, short-term exposure to 2 % O2 significantly enhanced the deposition of glycosaminoglycans compared to exposure to 5 % O2. Combining such microtissues with a supporting MEW mesh enabled the development of a larger graft with controlled geometry. In conclusion, this study highlights the potential of hMSC-derived cartilage microtissues, primed under altered oxygen environments, as building blocks for the biofabrication of articular cartilage grafts when combined with supporting MEW meshes.
PUBLISHED
Cited by: 0
Keywords: Tissue engineering; Mesenchymal stem/stromal cells; Microtissues; Hyaline articular cartilage; Oxygen; Glycosaminoglycans; Modular assembly; MEW mesh; microtissues; Melt electrowritten (MEW) meshes